2022
DOI: 10.1093/mnras/stac354
|View full text |Cite
|
Sign up to set email alerts
|

SDSS-IV MaNGA: spatial resolved properties of kinematically misaligned galaxies

Abstract: We select 456 galaxies with kinematically misaligned gas and stellar components from 9546 parent galaxies in MaNGA, and classify them into 72 star-forming galaxies, 142 green-valley galaxies and 242 quiescent galaxies. Comparing the spatial resolved properties of the misaligned galaxies with control samples closely match in the Dn4000 and stellar velocity dispersion, we find that: (1) the misaligned galaxies have lower values in Vgas/σgas and Vstar/σstar (the ratio between ordered to random motion of gas and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 76 publications
1
17
0
Order By: Relevance
“…High fractions of misaligned, i.e. not restricted to counter-rotating co-planar disks but in the range 30<Δ PA<150 degrees have also been reported in observational and simulation studies as a common kinematic characteristic for early type galaxies (Pizzella et al 2004;Davis et al 2011;Bryant et al 2019;Duckworth et al 2019;Duckworth, Tojeiro, & Kraljic 2020;Khim et al 2020;Xu et al 2022). We can estimate an upper limit to the fraction of gaseous counterrotators for the S0 class in our sample.…”
Section: The Frequency Of Counter-rotating Galaxiessupporting
confidence: 71%
See 1 more Smart Citation
“…High fractions of misaligned, i.e. not restricted to counter-rotating co-planar disks but in the range 30<Δ PA<150 degrees have also been reported in observational and simulation studies as a common kinematic characteristic for early type galaxies (Pizzella et al 2004;Davis et al 2011;Bryant et al 2019;Duckworth et al 2019;Duckworth, Tojeiro, & Kraljic 2020;Khim et al 2020;Xu et al 2022). We can estimate an upper limit to the fraction of gaseous counterrotators for the S0 class in our sample.…”
Section: The Frequency Of Counter-rotating Galaxiessupporting
confidence: 71%
“…Li et al (2021) based on MaNGA (Mapping Nearby Galaxies at APO) MPL-8 (MaNGA Product Launches 8th version) identified hundreds of misalignment galaxies with morphological features indicating merging or interaction. In addition, Xu et al (2022) discuss the global characteristics of misalignment galaxies found in MaNGA MPL-10.…”
Section: Introductionmentioning
confidence: 99%
“…They show that the central starformation activity of SF misaligned galaxies is several times higher than the average of local SF galaxies within central 1kpc. Based on a larger sample, Xu et al (2022) discover that the central region of misaligned SF galaxies have higher sSFR in comparison with their control samples, and the misaligned galaxies shows smaller central D 𝑛 4000 indicating younger stellar populations in SF and GV misaligned galaxies. For the QS misaligned galaxies, the H and molecular gas deficiency could be due to a selection bias that progenitors with lower gaseous contents are easier to show kinematic misalignments, since the lack of interaction between accreted and pre-existing gas.…”
Section: Gaseous Contentmentioning
confidence: 89%
“…This is the largest gas-star kinematically misaligned sample so far. As a complementary work of Xu et al (2022), we study the global properties of the misaligned galaxies. The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous studies (Lagos et al 2015;Davis & Bureau 2016;Bryant et al 2019;Xu et al 2022), we assume that galaxies with a misalignment angle of less than 30 • are aligned, galaxies with 30 • < Ψ gas < 150 • are misaligned, and galaxies with 150 • < Ψ gas < 180 • could be considered to be counter-rotating. However, this cut-off is rather arbitrary, and in addition, the measurement errors (specifically PA kin for slow rotators) can be large, and the PAs are projected values, together resulting in an uncertainty on the Ψ gas misalignment.…”
Section: Misalignment Between Gas and Stars (ψ Gas )mentioning
confidence: 99%